2018
DOI: 10.1111/epi.14084
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiac stiffness is associated with autonomic dysfunction in patients with temporal lobe epilepsy

Abstract: Autonomic dysfunction is linked to sudden death regardless of the presence of structural heart disease. The pathway from autonomic dysfunction to sudden death is not fully understood, but myocardial sympathetic stimulation leading to arrhythmia and/or cardiac fibrosis might play a role. Our goal was to evaluate cardiac stiffness by echocardiography and its association with clinical, structural, and autonomic variables in people with epilepsy (PWE) compared to healthy controls. A 12-lead electrocardiogram, trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 18 publications
(50 reference statements)
0
30
0
3
Order By: Relevance
“…Moreover, a recent study found increased cardiac stiffness among young patients with temporal lobe epilepsy without preexisting cardiovascular disease. Regression analyses noted autonomic dysfunction to be responsible for more than 50% of this cardiac abnormality . Furthermore, postmortem examination has revealed irreversible perivascular and interstitial fibrosis of the myocardium among cases of SUDEP, absent in healthy individuals who died of other causes …”
Section: Pathophysiology Of Altered Cardiac Ion Channel Expression Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent study found increased cardiac stiffness among young patients with temporal lobe epilepsy without preexisting cardiovascular disease. Regression analyses noted autonomic dysfunction to be responsible for more than 50% of this cardiac abnormality . Furthermore, postmortem examination has revealed irreversible perivascular and interstitial fibrosis of the myocardium among cases of SUDEP, absent in healthy individuals who died of other causes …”
Section: Pathophysiology Of Altered Cardiac Ion Channel Expression Inmentioning
confidence: 99%
“…Regression analyses noted autonomic dysfunction to be responsible for more than 50% of this cardiac abnormality. 36 Furthermore, postmortem examination has revealed irreversible perivascular and interstitial fibrosis of the myocardium among cases of SUDEP, absent in healthy individuals who died of other causes. 37 Animals with epilepsy exhibit similar features of structural cardiac disease, with evidence of an autonomic contribution.…”
Section: Structural Cardiac Disease In Epilepsymentioning
confidence: 99%
“…Bei Status-und Epilepsie-Patienten finden sich zum Teil vermehrte ventrikuläre, fibrotische Umbauprozesse und Kontraktionsbandnekrosen, die ihrerseits arrhythmogen wirken können [46,47]. Bei SUDEP-Patienten finden sich strukturelle Herzveränderungen im Vergleich zu anderen Epilepsiepatienten zwar nicht häufiger [48], dennoch scheint es plausibel, dass ein Teil der plötzlichen Todesfälle von Epilepsiepatienten primär auf einen plötzlichen Herztod (unabhängig vom erwähnten neurovegetativen Zusammenbruch) zurückzuführen ist und in diesen Fällen der plötzliche Herztod und SUDEP überlappende Entitäten sind [49].…”
Section: Sudep Als Plötzlicher Herztod?unclassified
“…Existem, todavia, relatos de morte súbita nos pacientes por disfunção cardíaca de caráter taquiarritmogênico -como fibrilação ventricular ou taquicardia ventricular. 60 O desfecho dessa via fisiopatológica se traduz no grave comprometimento da função cardiopulmonar mediada centralmente decorrente da convulsão, com uma apneia terminal normalmente precedendo assistolia e óbito 28,33,[61][62][63] .…”
Section: Fisiopatologiaunclassified
“…Nos modelos animais, a cronicidade e a elevada frequência das crises epilépticas se relacionam a um aumento da pressão arterial média, da frequência cardíaca em repouso e da susceptibilidade a arritmias induzidas por isquemia e reperfusão 28,[76][77][78][79][80] . É possível que essa disautonomia crônica predisponha a uma fibrose miocárdica e seja um substrato anatômico arrítmico para a morte súbita 60 .…”
Section: Função Cardiorrespiratória E Controle Autonômicounclassified